Regionalização de inversores de frequência de média tensão em painéis: estudo de caso - Cruz, Luiz Antonio Melaninho (Universidade Estadual Paulista (Unesp), 2021)
In order to understand the reasons that lead a multinational company to adopt a business model, based on import and resale or manufacturing in the national territory, this work was carried out using the methodology known as case study. The case studied is a study carried out by a multinational company, already consolidated in the market, with an experience of one hundred and fifty years operating in Brazil. The present work forms points for the company to verify the feasibility of creating a medium voltage frequency inverter factory in Brazil, in order to reduce costs, delivery time and make the products more attractive in the South American market. were raised using the work: “Import conditions for distributed photovoltaic mini & microgeneration equipment in Brazil”, by author Roberto Devienne Filho. Based on the work of Devienne Filho, it was possible to compare the terms and cost generated by imports with the cost of domestic manufacturing. Despite reducing the reduction in terms and costs of producing in Brazil, due to the lack of knowledge of the national industry in manufacturing chips and known semiconductors, it is not feasible to switch to the national production model.

Com o intuito de entender os motivos que levam uma empresa multinacional a adotar um modelo de negócio, baseado na importação e revenda ou na fabricação em território nacional, este trabalho foi realizado utilizando a metodologia conhecida como estudo de caso. O caso estudado se trata de um estudo feito por uma empresa multinacional, já consolidada no mercado, com experiência de cento e cinquenta anos atuando no Brasil. O presente trabalho levantou pontos analisados pela empresa para verificar a viabilidade de criar uma fábrica de inversores de frequência de média tensão no Brasil, para assim, diminuir os custos, prazo de entrega e tornar os produtos mais atrativo no mercado da América do Sul. Esses pontos foram levantados utilizando o trabalho: “Condições de importação de equipamentos de mini & microgeração distribuída fotovoltaica no Brasil”, do autor Roberto Devienne Filho. Com base no trabalho de Devienne Filho foi possível fazer uma comparação dos prazos e custos gerados pela importação com o custo da fabricação nacional. Apesar de mostrado a diminuição no prazo e custo de se produzir no Brasil, em razão da falta de conhecimento da indústria nacional em fabricar chips e semicondutores mostrou-se inviável mudar para o modelo de produção nacional.
Keywords: Frequency inverters; Domestic manufacturing; Import and resale; Importação e revenda; Inversores de frequência; Fabricação nacional